Intuitive Dynamics: The Inscription of Time in MnG House - Prasertsuk, Santirak (Journal of Architectural/Planning Research and Studies (JARS), 2022)
For a decade, the architectural work of an architect Pornchai Boonsom has been based on an exploration in ‘time’ and ‘dynamic movement’ of interactive forces in the context of Postmodernism and Consumerism in Thailand. His MnG House in Bangkok, completed in 2002, is a reflection of a new thinking in science, particularly an experiment on Henri Bergson’s philosophical concepts of the evolution of time and dynamic process of intuition. In the early twentieth century, Bergson proposed what became the great breakthrough against the classical biology of Charles Darwin - the theory of evolution. He introduced a new notion of time as a ceaseless flow or flux – not a discrete unit. This concept has changed the way we understand life and universe, and the way we spatially conceive and perceive architecture through a linear time. Bergson’s another concept of intuition psychologically explains how we understand the reality of the world as a continual flow of life. Pornchai Boonsom’s MnG House reflects the Bergsonian worldview both in architectural geometry and spatial expression. The house could be defined as ‘the inscription or the writing of time’ through architectural productions: an exemplar work manifesting a continual change of form without a beginning or an end.